Blood money [videorecording (DVD)] - Coltrane, Ellar, 1994-; Fitzgerald, Willa; Artist, Jacob; Cusack, John, 1966- (Lionsgate, 2017)
Three friends on a wilderness excursion stumble upon bags of money and must outrun a white collar criminal hell bent on retrieving his fortune.